Penegakan Hukum terhadap Tindak Pidana Korporasi di Bidang Lingkungan Hidup - Ismaidar Ismaidar; Muhammad Aldin; August Saut Maringan Sihombing (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Corporate crime in the environmental sector is one of the biggest challenges in law enforcement in Indonesia. Companies that pollute or destroy the environment are often difficult to hold criminally liable due to the impersonal nature of their legal entities. This study aims to analyze the effectiveness of law enforcement against corporations that commit environmental crimes and the obstacles faced by law enforcement officials in proving and imposing crimes against corporations. The method used is normative juridical with a legislative approach and case studies. This research found that although there is already a fairly strong legal framework, such as in Law No. 32 of 2009 and the new Criminal Code, implementation in the field is still weak. Some of the inhibiting factors include the difficulty of proving the responsibility structure in the corporation, the lack of investigator capacity, and the influence of economic power from corporations. Therefore, it is necessary to strengthen regulations, apparatus capacity, and corporate criminal accountability mechanisms that are more adaptive and firm.